Molecular ablation of tumor blood vessels inhibits therapeutic effects of radiation and bevacizumab. Issue 10 (12th April 2018) - Yadav, Viveka Nand; Altshuler, David; Kadiyala, Padma; Zamler, Daniel; Comba, Andrea; Appelman, Henry; Dunn, Patrick; Koschmann, Carl; Castro, Maria G; Löwenstein, Pedro R
Abstract: Background: Glioblastoma (GBM) is an aggressive and highly vascular tumor with median survival below 2 years. Despite advances in surgery, radiotherapy, and chemotherapy, survival has improved modestly. To combat glioma vascular proliferation, anti-angiogenic agents targeting vascular endothelial growth factor (VEGF) were introduced. Preclinically these agents were effective, yet they did not improve overall survival in phase III trials. We tested the hypothesis that ganciclovir (GCV)-mediated killing of proliferating endothelial cells expressing herpes simplex virus type 1 thymidine kinase (HSV1-TK) would have direct antitumor effects, and whether vessel ablation would affect the antitumor activity of anti-VEGF antibodies and radiotherapy. Methods: Proliferating endothelial cells were eliminated using GCV-mediated killing of proliferating endothelial cells expressing HSV1-TK (in Tie2-TK-IRES-GFP mice). Syngeneic NRAS/p53 (NP) gliomas were implanted into the brains of Tie2-TK-IRES-GFP mice. Endothelial proliferation activates the Tie2 promoter and HSV1-TK expression. Administration of GCV kills proliferating tumor endothelial cells and slows tumor growth. The effects of endothelial cell ablation on anti-angiogenic therapy were examined using anti-VEGF antibodies or irradiation. Results: GCV administration reduced tumor growth and vascular density, increased tumor apoptosis, and prolonged survival. Anti-VEGF antibodies or irradiation also prolonged survival. Surprisingly, combining GCV with irradiation, or with anti-VEGF antibodies, reduced their individual therapeutic effects. Conclusion: GCV-mediated killing of proliferating endothelial cells expressing HSV1-TK, anti-VEGF antibodies, or irradiation all reduced growth of a murine glioma. However, elimination of microvascular proliferation decreased the efficacy of anti-VEGF or irradiation therapy. We conclude that, in our model, the integrity of proliferating vessels is necessary for the antiglioma effects of anti-VEGF and radiation therapy.